(untitled) (Medical Forum Monthly, 2023)
Objective: The current study was conducted to estimate AUB in various age groups, to study histopathology of the endometrium in cases of AUB and to assay the clinicopathological patterns. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Pathology Department of BMSI, JPMC Karachi Sindh Pakistan from January 2020 to December 2022. Materials and Methods: 81 cases of AUB were included in this study. All cases of Endometrial samples such as endometrial biopsy, dilatation and curettage material (D&C), were thoroughly reviewed and were included in this study, taking into account their age, patient’s characteristics, clinical information and the histopathological findings obtained. Results: The age group of patients in this study ranged from 22 to 64 years. The maximum number of cases 50 (61.8%) were in the age group of 20 to 39 years. The endometrial polyp (37%) was found to be the most common histopathological pattern followed by endometritis (18.5%) and secretory phase endometrium (18.5%). It was found that 12.4% of cases were due to proliferative phase epithelium, 4.9% were malignancies, and 7.5% were hyperplastic. Conclusion: In conclusion, abnormal uterine bleeding has different histo-morphological findings among different age groups, and non-structural causes are more common than structural ones. All three age groups are susceptible to Endometrial Polyps, which are the most prevalent. All cases of malignancies were present in postmenopausal women. Therefore, it is imperative to evaluate the endometrial biopsies of postmenopausal women.